Two-tag purification of recombinant proteins for the construction of solid matrix-antibody-antigen (SMAA) complexes as vaccines. - Randall, R; Hanke, T; Young, D; Southern, J (1993)
In order to facilitate the purification of recombinant proteins for immunization purposes, for example through the construction of solid matrix-antibody-antigen (SMAA) complexes, two small but different tag sequences were attached to the N- and C-termini of recombinant proteins. The 12-amino-acid N-terminal tag (His) contained an array of six histidines which permitted first-step purification by nickel-affinity column chromatography. The C-terminal tag (Pk) was a 14-amino-acid oligopeptide recognized by the monoclonal antibody (mAb) SV5-P-k. The mAb SV5-P-k was linked to a solid matrix and the solid matrix-antibody complexes were saturated with PK-linked recombinant antigens to generate SMAA complexes. The procedure used for construction of the SMAA complexes also acted as a second purification step. Neither of the tag sequences was cleaved from the recombinant proteins before immunization. This two-step purification procedure was used to construct SMAA complexes containing either p17 or reverse transcriptase (rt) of simian immunodeficiency virus (SIV). Mice immunized with these complexes had high antibody titres recognizing both the respective recombinant and native SIV proteins. A weak antibody response was also measured against both the terminal tags. The advantages of using simple dual purification procedures for isolating tag-linked recombinant proteins for use in vaccines are discussed.